Bacterial endophytes of weeds are effective biocontrol agents of Agrobacterium spp., Pectobacterium spp., and promote growth of tomato plants - KRIMI, Zoulikha; ALIM, Djamila; DJELLOUT, Hafédha; TAFIFET, Lamia; MOHAMED-MAHMOUD, Fadhéla; RAIO, Aida (Phytopathologia Mediterranea, 2016)
Bacterial endophytes were isolated from native plants growing in a fallow field. Taxonomy of these bacteria, and their beneficial effects to plants, were determined. Seventeen strains were selected from a group of 73 isolates on the basis of origin, colony morphology and antagonistic properties and were characterized by 16S rRNA gene sequence and phylogenetic analyses. These strains were assayed in vivo against pathogenic strains of Agrobacterium and Pectobacterium spp. Their ability to improve plant growth was also evaluated. The Gram positive Bacillus amyloliquefaciens, B. cereus, B. methylotrophicus, B. pumilus and Curtobacterium flaccumfaciens and the Gram negative Pseudomonas brassicacearum were identified. The Bacillus and Pseudomonas were shared among five plant species while C. flaccumfaciens was isolated only from Euphorbia spp. Biocontrol activity of endophytic strains was evaluated on potato disks inoculated with Pectobacterium spp. and on tomato plants grown in sterile soil, root-bacterized with endophytes and stem inoculated with Agrobacterium spp. A reduction of soft rot caused by Pectobacterium spp. on three potato varieties treated with Bacilluss pp. strains was observed. Bacillus methylotrophicus strain OS4 strongly reduced gall development induced by Agrobacterium spp. and gave 100% germination of tomato seeds compared with 75.5% for the non-treated seeds. Pseudomonas brassicacearum strain PS1 enhanced tomato seed germination and increased plant growth parameters. These results indicate that native plants harbour various endophytic bacterial species that possess potentially valuable biocontrol and growth promotion activities.